Composition‐ and Temperature‐Dependent Large Strain in (1−x)(0.8Bi0.5Na0.5TiO3–0.2Bi0.5K0.5TiO3)– xNaNbO3 Ceramics. Issue 4 (26th December 2014) - Dong, Guangzhi; Fan, Huiqing; Shi, Jing; Li, Mengmeng; Jo, W.
<x xml:space="preserve">Abstract</x> Ternary solid solutions of (1 − x)(0.8Bi0.5Na0.5TiO3–0.2Bi0.5K0.5TiO3)– xNaNbO3 (BNKT–xNN) lead‐free piezoceramics were fabricated using a conventional solid‐state reaction method. Pure BNKT composition exhibited an electric‐field‐induced irreversible structural transition from pseudocubic to ferroelectric rhombohedral phase at room temperature. Accompanied with the ferroelectric‐to‐relaxor temperature TF‐R shifted down below room temperature as the substitution of NN, a compositionally induced nonergodic‐to‐ergodic relaxor transition was presented, which featured the pinched‐shape polarization and sprout‐shape strain hysteresis loops. A strain value of ~0.445% (under a driving field of 55 kV/cm) with large normalized strain of ~810 pm/V was obtained for the composition of BNKT–0.04NN, and the large strain was attributed to the reversible electric‐field‐induced transition between ergodic relaxor and ferroelectric phase.